Localization: Customizing Software for the World - Karsch, Barbara Inge; Bansleben, Erik (Language at Work - Bridging Theory and Practice, 2009)
The Professional & Continuing Education (PCE) division at University of Washington (in Seattle, United States) is launching a new Certificate program this year in localization. Officially named Localization: Customizing Software for the World, the program is comprised of a 3-course intensive format that was developed in partnership with industry, professional organizations, and academia.